2016
DOI: 10.1148/radiol.2015150486
|View full text |Cite
|
Sign up to set email alerts
|

Is the Relationship between Cortical and White Matter Pathologic Changes in Multiple Sclerosis Spatially Specific? A Multimodal 7-T and 3-T MR Imaging Study with Surface and Tract-based Analysis

Abstract: Purpose:To investigate in vivo the spatial specificity of the interdependence between intracortical and white matter (WM) pathologic changes as function of cortical depth and distance from the cortex in multiple sclerosis (MS), and their independent contribution to physical and cognitive disability. Materials and Methods:This study was institutional review board-approved and participants gave written informed consent. In 34 MS patients and 17 age-matched control participants, 7-T quantitative T2* maps, 3-T T1-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 39 publications
0
7
0
1
Order By: Relevance
“…Thirty-one patients (21 females; mean age = 42.4 ± 8.7 SD years) were prospectively recruited in the study from May 2010 to May 2013. This cohort is partly overlapping (31 out of 41 patients) with a cohort from a previously published study in which we found cortical areas characterized by longer q-T 2 * relative to a healthy matched population (Louapre et al, 2016, Louapre et al, 2015, Mainero et al, 2015). The remaining 10 MS subjects were not included due to the lack of NP evaluation at the time of the scanning procedure.…”
Section: Methodsmentioning
confidence: 59%
“…Thirty-one patients (21 females; mean age = 42.4 ± 8.7 SD years) were prospectively recruited in the study from May 2010 to May 2013. This cohort is partly overlapping (31 out of 41 patients) with a cohort from a previously published study in which we found cortical areas characterized by longer q-T 2 * relative to a healthy matched population (Louapre et al, 2016, Louapre et al, 2015, Mainero et al, 2015). The remaining 10 MS subjects were not included due to the lack of NP evaluation at the time of the scanning procedure.…”
Section: Methodsmentioning
confidence: 59%
“…Furthermore, there are similarities between the average anatomical distribution of GM atrophy and the distributions of both existing WM lesions ( Bodini et al, 2009 ; Muhlau et al, 2013 ; Riccitelli et al, 2012 ) and new WM lesions ( Battaglini et al, 2009 ; Bendfeldt et al, 2010 ). The relation of local GM atrophy to lesional and non-lesional damage in connected WM tracts has only been partially explored ( Bergsland et al, 2015 ; Louapre et al, 2016 ; Steenwijk et al, 2015 ) and further studies are needed to clarify this.…”
Section: Challenges Of Pathology Physiology and Treatment Effectsmentioning
confidence: 99%
“…Tracts of the limbic system, like the fornix, play crucial roles in aspects of cognition, memory, behavior, and reasoning (Catani & de Schotten, 2012), and they have been implicated in the above whole-brain analyses of MS. Given this relevance, limbic system tracts have been the focus in MS diffusion MRI studies assessed with either region of interest/atlas (Dineen, Bradshaw, Constantinescu, & Auer, 2012;Koenig et al, 2013;Mesaros et al, 2012;Van Geest et al, 2018) or tractography (Fink et al, 2010;Kern et al, 2015;Keser et al, 2017;Louapre et al, 2016;Syc et al, 2013), both targeted analyses that can have distinct advantages over whole-brain voxel-based methods (e.g., far fewer multiple comparisons and do not need intersubject registration for native space tractography). The majority of these DTI studies have been in patients with RRMS, but FA abnormalities in the limbic WM tracts, including the fornix, have also been demonstrated in primary progressive (PPMS; Bodini et al, 2009) and secondary progressive MS (SPMS) (Meijer et al, 2016).…”
mentioning
confidence: 99%